Hypoxia supports differentiation of terminally exhausted CD8 T cells - Bannoud, Nadia (2021)
Hypoxia, angiogenesis, and immunosuppression have been proposed to be interrelated events that fuel tumor progression and impair the clinical effectiveness of anti-tumor therapies. Here we present new mechanistic data highlighting the role of hypoxia in fine tuningCD8 T cell exhaustion in vitro, in an attempt to reconcile seemingly opposite evidence regarding the impact of hypoxia on functional features of exhausted CD8 T cells.Focusing on the recently characterized terminally-differentiated and progenitor exhausted CD8 T cells, we found that both hypoxia and its regulated mediator, vascular endothelial growth factor (VEGF)-A, promote the differentiation of PD-1+ TIM-3+ CXCR5+ terminally exhausted-like CD8 T cells at the expense of PD-1+ TIM-3- progenitor-like subsets without affecting tumor necrosis factor (TNF)-a and interferon (IFN)-g production or granzyme B(GZMB) expression by these subpopulations. Interestingly, hypoxia accentuated the proangiogenic secretory profile in exhausted CD8 T cells. VEGF-A was the main factor differentially secreted by exhausted CD8 T cells under hypoxic conditions. In this sense,we found that VEGF-A contributes to generation of terminally exhausted CD8 T cellsduring in vitro differentiation. Altogether, our findings highlight the reciprocal regulation between hypoxia, angiogenesis, and immunosuppression, providing a rational basis to optimize synergistic combinations of antiangiogenic and immunotherapeutic strategies,with the overarching goal of improving the efficacy of these treatments.